Pengaruh Induksi Autotomi pada Kepiting Bakau (Scylla serrata, Scylla tranquebarica, Scylla paramamosain) terhadap Sintasan, Molting, dan Pertumbuhan di Tambak Rakyat Kelurahan Anggoeya Kendari-Sulawesi Tenggara - Muhammad Fajar Purnama; La Ode Aliman Afu; Haslianti Haslianti (Jurnal FishtecH, 2016)
Mud crab is one of brackish water commodity with high ecological and economical value, which is a lot of demand from the local, regional and also foreign market. This study aims to determine autotomi induction effect on the survival rate, molting, and growth of the mud crab (Scylla serrata, Scylla tranquebarica, and Scylla paramamosain). This research was conducted in November-January 2013, which is located in the traditional ponds in Anggoeya Village, Poasia District, Municipality of Kendari, Southeast Sulawesi. It used a completely randomized design (CRD) with 3 treatments and 3 replications, thus in this study, theirs 9 units of experiments which each experimental unit consisted of 10 crabs test. Treatment was applied in this study is the autotomi induction treatment on the mud crab S. paramamosain, S. tranquebarica, and S. serrata. Data were analyzed by analysis of variance (ANOVA). If the results showed the significant effect, it would proceed by the least significant difference (LSD) at the 95% confidence level (Î± = 0,05). As a tool to carried out the statistical tests were used the SPSS version 17.0 program package. The results showed that autotomi induction treatment on the different types significantly the different results (p<0,05) to the survival rate and molting perfection, but it was not significantly different (p>0,05) to the absolute growth and molting period of the mud crab (S. paramamosain, S. tranquebarica, and S. serrata).